ANALYZING POLITENESS STRATEGIES IN ONLINE LEARNING INTERACTIONS AMONG ENGLISH EDUCATION STUDENTS - Nurmayana; Fatin Nadifa Tarigan; Linda Astuti Rangkuti; Nurhalimah (Esteem Journal of English Education Study Programme, 2025)
This research investigates the types and frequency of politeness strategies employed by English Education students during online academic interactions via WhatsApp, with a particular emphasis on how students uphold politeness and demonstrate respect toward lecturers within a virtual learning environment. Utilizing a descriptive qualitative approach, the study analyzed 200 utterances derived from constructed chat transcripts. The data were examined through the lens of Brown and Levinson’s (1987) politeness theory, encompassing positive politeness, negative politeness, bald on record, and off record strategies. Findings indicate that positive politeness strategies predominated (57.5%), followed by negative politeness strategies (30%), with bald on record and off record approaches appearing less frequently. This distribution highlights the students’ pragmatic awareness and the influence of cultural norms in sustaining courteous academic discourse. The study contributes to the fields of linguistics, pragmatics, and English language education by offering insights into students’ digital communicative behavior. It also informs educators and teacher preparation programs about the pragmatic competencies necessary for professional interaction in online academic spaces. The novelty of the study lies in its focus on the simulated digital exchanges of English Education students, bridging theoretical pragmatics with pedagogical application, and enriching the discourse on digital pragmatics within the Indonesian higher education landscape.